Optimization of Early Mobilization Program for Patients With Acute Ischemic Stroke: An Orthogonal Design - Zhang, Min; Wang, Qing; Jiang, Yuanyuan; Shi, Huiling; Peng, Tiantian; Wang, Mengyue (Frontiers in Neurology, 2021)
Background and purpose: Early mobilization is considered to have favorable outcomes for stroke patients, but there is currently a lack of specific data to guide this early mobilization, including the initiation time, intensity, frequency, and duration of each activity. Therefore, the optimal strategy for early mobilization is unclear. In this study, we investigated the best combination of different factors to achieve early mobilization, to develop the optimal program. Methods: We conducted an L9 (33) orthogonal experiment with a blinded follow-up assessment. Patients with ischemic stroke, admitted to a stroke unit within 24–72 h of its onset, were recruited. Eligible subjects were randomly assigned to one of nine different programs of early mobilization. The outcomes were assessed at baseline, discharge, and 1 month and 3 months after discharge to observe the changes in various efficacy indicators and determine the main factors affecting outcome. Results: We analyzed 57 of 63 patients, after six were excluded for poor compliance, failure to cooperate with the study, or worsening of the disease. The initiation time, intensity, and frequency of mobilization were the main factors affecting outcome (all P < 0.05), and the duration of each activity was a secondary factor (P > 0.05). A comprehensive analysis of the various parameters showed that the optimal level of the early mobilization program was an initiation time: 24–48 h after stroke; intensity: bed and chair transfer, sitting out of bed, standing and walking or climbing stairs when mobility permitted; frequency: 2–3 times/day; duration of each mobilization: determined according to the actual situation of the patient. Conclusions: Early rehabilitation with high-intensity physical exercise at 24–48 h after the onset of stroke, 2–3 times/day, may benefit stroke patients. Applying the optimized program of early mobilization to stroke patients effectively alleviated their symptoms of neurological deficit, improved their capacity for self-care, restored their self-efficacy, improved their quality of life and social participation, and reduced post-stroke fatigue at 3 months.